Wars Have Become Too Cheap to Boost Growth - Jonathan Nitzan; Shimshon Bichler (The Bichler and Nitzan Archives, 2019)
FROM THE NOTE: This week, with the Federal Reserve Banks of New York and Atlanta anticipating sharply lower GDP growth for 2019:Q1, President Trump presented a `Budget for A Better America', calling for a smaller government and a bigger military. Forty years ago, the very same call was hailed as the best recipe for renewed growth. The U.S. ruling class was getting ready to install Ronald Reagan as President, abandon the Cold War and embark on neoliberalism, and it argued that, for that shift to succeed, the country needed a leaner government in order to unleash its entrepreneurial spirit and crowd-in private investment, and that it required a strong military in order to boost its global muscle and open world markets for its products and capital. Ideology aside, one key reason for the growth optimism of the time was rising military spending…
Keywords: L64; E62; P16; D74; 330; economic growth; military spending